Relationship between Motion Sickness and Balance - Snehal Joshi (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
The exact cause of motion sickness is unknown. This vestibular malfunction can be associated with motion sickness. Hence there is a possibility of impaired balance in individuals with motion sickness.